2005
DOI: 10.1523/jneurosci.3034-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Soluble β-Amyloid1-40Induces NMDA-Dependent Degradation of Postsynaptic Density-95 at Glutamatergic Synapses

Abstract: Amyloid-␤ (A␤) has been implicated in memory loss and disruption of synaptic plasticity observed in early-stage Alzheimer's disease. Recently, it has been shown that soluble A␤ oligomers target synapses in cultured rat hippocampal neurons, suggesting a direct role of A␤ in the regulation of synaptic structure and function. Postsynaptic density-95 (PSD-95) is a postsynaptic scaffolding protein that plays a critical role in synaptic plasticity and the stabilization of AMPA (AMPARs) and NMDA (NMDARs) receptors at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
204
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(220 citation statements)
references
References 71 publications
15
204
1
Order By: Relevance
“…In addition, the prevention of the decrease in synaptic markers found in treated mice showed that lithium and rosiglitazone prevent synaptic failure found in models of AD. 42,43,74,75 These changes correlate with an enhanced performance in our memory flexibility test, suggesting that hippocampal synaptic function is improved under both treatment conditions.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the prevention of the decrease in synaptic markers found in treated mice showed that lithium and rosiglitazone prevent synaptic failure found in models of AD. 42,43,74,75 These changes correlate with an enhanced performance in our memory flexibility test, suggesting that hippocampal synaptic function is improved under both treatment conditions.…”
Section: Discussionmentioning
confidence: 67%
“…The attack on synapses inhibits long-term potentiation (LTP) (11,13,14), a classic paradigm for memory-related synaptic mechanisms. ADDL binding further induces AD-like pathology including neuronal tau hyperphosphorylation (15), oxidative stress (16), and synapse deterioration and loss (17)(18)(19)(20)(21). The pathological relevance of ADDLs has been substantiated by their disease-specific accumulation in human brain and CSF (1,22) and by the accumulation of structurally equivalent oligomers in transgenic mouse AD models (23).…”
mentioning
confidence: 99%
“…Furthermore, the densities of NMDA receptors are decreased (Wakabayashi et al, 1999;Paneggress et al, 2002). Recent studies suggest that glutamate receptors may be involved in Aβ-induced synaptic dysfunction (Snyder et al, 2005;Tyszkiewicz and Yan, 2005;Floden at al., 2005), and soluble Aβ-40 can induce NMDA-dependent degradation of a postsynaptic density-95 protein within glutamatergic synapses (Roselli et al, 2005). In future studies, it would be important to determine whether specific synapse types (glutamatergic versus GABA) are differentially reduced in proximity to β-amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%